Comparison of Conventional, Complementary and Distraction Therapies to Reduce Dysmenorrhea in Adolescents - Khotimah, Husnul; Rahayu, Antika Maulida; Rahayu, Sri; Soraya, Kety (Fakultas Ilmu Kesehatan, 2025)
Menstruation is one of the changes experienced by adolescent girls. During this period, women often experience discomfort such as dysmenorrhea, which can affect physical health and daily activities. The incidence of dysmenorrhea remains high worldwide and in Indonesia, but it can be managed through both pharmacological and non-pharmacological methods. The purpose of this study was to determine the effectiveness of conventional, complementary and diversion therapy in overcoming dysmenorrhea in adolescents. The study design was a retrospective cohort. The sample used was 35 using a purposive sampling technique at MTsN 1 Serang Regency in March-April 2025. Data analysis used in this study was the Wilcoxon Test and Kruskal-Wallis Test. The results showed that there was a significant relationship between post-test results and pre-test in complementary therapy (p = 0.005) and diversion therapy (p = 0.007) with dysmenorrhea, while conventional therapy (p = 0.458) did not have a significant relationship with dysmenorrhea. Overall, the three therapies had a significant effect on dysmenorrhea (p <0.001). The post-test results of the three therapies were analyzed and found that there was no significant relationship with dysmenorrhea (p = 0.812). This indicates that complementary and diversional therapies have comparable effectiveness in reducing dysmenorrhea pain. It is hoped that medical personnel and adolescents can begin to consider integration strategies to treat dysmenorrhea pain.